재한외국인의 주거실태 및 주거만족도에 관한 연구 -서울, 경기 지역을 중심으로 - 김영주; 박동; Kim, Young-Joo; Bo, Tong (한국콘텐츠학회 논문지, 19(1), 2019)
The purpose of this study was to investigate housing situation and residential satisfaction of foreigners in Korea, and to identify influential factors for housing satisfaction. A questionnaire survey was conducted to 132 foreigners who reside in Seoul and Gyeonggi-do. Most of the respondents were Chinese and the average age was 45.7. Over 90% of the respondents lived in a rented house and detached house was the most popular type of house. Overall score of residential satisfaction was 3.43 and it was above average. However, scores for parking lot, housing deterioration, and space planning showed the lowest level of satisfaction. Factor analysis was used to summarize the variables related to residential satisfaction and 5 factors -'space planning and organization,' 'amenities & equipment', 'community facilities,' 'near environment' and 'housing expenses'- were drawn. Among those, 'space planning and organization' was the most influential factor to residential satisfaction as the result of multiple regression analysis. 본 연구는 재한외국인의 주거실태와 주거만족도를 조사하고 이들의 주거만족도에 영향을 미치는 요인을 파악하는 것을 목적으로 한다. 이를 위해 서울 및 경기도에 거주하는 재한외국인을 대상으로 설문조사를 실시하였으며 총 132부의 설문을 최종 분석에 사용하였다. 분석 결과 응답자들은 대부분 중국국적으로 평균연령은 45.7세였다. 주택소유형태는 90% 이상이 차가였으며, 주택유형은 단독주택이 가장 많았다. 전반적인 주거만족도 점수는 3.43점으로 보통 이상이었으나 주차공간과 노후도, 공간구성에 대한 만족도가 가장 낮았다. 주거만족도 변수에 대한 요인분석 결과 '공간계획 및 구성,' '시설설비,' '생활편의시설,' '생활환경,' '주거비부담'과 관련된 5개 요인이 도출되었다. 이들 5개 요인이 주거만족도에 미치는 영향을 파악하기 위한 중회귀분석 결과 '공간계획 및 구성'과 관련된 요인의 영향이 가장 큰 것으로 나타났다.